THE CLASSIFICATION OF AVIATION ACTIVITY - Похиленко, Ірина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose: the purpose of this article is to summarize and systematize approaches to the classification of aviation activities and distinguish significant classification criteria from the point of view of their importance for the formation of mechanisms in this field. Research methods: using a dialectical cognition method allowed to concentrate accumulated scientific knowledge and practice of applying the current legislation for the implementation of the classification of aviation activity. Results: European integration tendencies lead the interest to aviation activity in terms of its future development prospects. These tasks cannot be reached without the regulatory influence of the state. Classification of aviation activity is of great theoretical and practical importance for the understanding of its nature and purpose. The issue of the classification of aviation activity is governed by the provisions of the Convention for the Unification of Certain Rules Relating to International Carriage by Air, Signed at Warsaw on 12 October 1929 (Warsaw Convention), Convention on International Civil Aviation done at Chicago on 7 December 1944 (Chicago Convention), the Convention on the International Recognition of Rights in Aircraft at Geneva on 19 June 1948 (Geneva Convention), the Convention for the Unification of Certain Rules for International Carriage by Air at Montreal on 28 May 1999 (Montreal Convention), the Air Code of Ukraine, the Law of Ukraine «On Transport», etc. The criterion of subjectivity is rather important in forming of aviation activity classification. Investigating the different classifications of aviation activity subjects, we can conclude that a comprehensive typology of aviation activity subjects is possible only through the use of a combination of several methods of their separation. Therefore, we suggest classifying the aviation activity subjects according to their legal form. By the number of subjects that perform state regulation of aviation activity they can be classified into: 1) authorities of general competence; 2) authorities of special competence in the field of aviation law compliance; 3) bodies of related competence. According to the payment criterion, aviation activity can be divided into paid and non-paid activity. Also aviation activity can be classified by subject orientation and by the legal force of normative legal act, which stipulates the procedure of aviation activity. Discussion: classification of aviation activity issues, criteria of aviation activity classification.